Redescription of the monotypic genus Volkeliopsis Poppius (Hemiptera: Heteroptera: Miridae: Bryocorinae) - Sadowska-Woda, Izabela; Chérot, Frédéric (Zootaxa, 2008)
The monotypic genus Volkeliopsis POPPIUS and its type species Volkeliopsis frontalis are redescribed. The male genital structures are described for the first time.